Tissue Kallikrein supplementation in ischemic phase protects the neurovascular unit and attenuates reperfusion-induced injury in ischemic stroke - Xiao Ran; Tingting Xu; Hang Ruan; Xiaochuan Wang; Qin Zhang (Elsevier, 2024)
Tissue kallikrein (TK) has emerged as a potential neuroprotective agent in ischemic stroke (IS), yet the optimal timing and mechanisms of TK therapy remain unclear. Here, we established a causal link between lower baseline TK levels and an increased risk of stroke through a retrospective, multicenter cohort study involving 2115 initially non-stroke subjects monitored for 5 years. Sequentially, we observed a notable increase in bradykinin receptor 2 (B2R) levels during the ischemic phase of the IS model, while levels of TK and bradykinin receptor 1 (B1R) remained stable. Intriguingly, both B1R and B2R exhibited a significant elevation 24 h after reperfusion. Further investigations in preclinical models demonstrated that TK supplementation activates the PI3K/AKT signaling pathway via enhanced B2R expression during the ischemic phase, leading to nuclear translocation of Hif-1α. This activation enhances the expression of VEGF and eNOS, thereby fortifying the neurovascular unit. Moreover, it suppresses the activation of the kallikrein-kinin system induced by reperfusion injury, effectively reducing inflammation, ROS production, apoptosis, and endothelial barrier dysfunction. Thus, our findings highlight the significance of TK supplementation during the ischemic phase in attenuating reperfusion-induced injury in IS, providing a mechanistic rationale for determining the optimal timing for TK supplementation therapy.